Inovasi Olahan Tahu Sebagai Varian Jajanan Baru di Surabaya - Raden Roro Ayunda Yahdis Sabila; Paulina Tjandrawibawa (Jurnal Vicidi, 2019)
The purpose of this research is to find out the potential of knowing tofu nuggets as a new variant of snacks in Surabaya. The research will be held in Surabaya and will begin on Tuesday 1 October 2019 until Wednesday 16 October 2019. Using a form of queationnaire that distributed online as the Quantitative method, an interviews as the qualitative methods and literature studies. This research involved 3 expert users and 3 extreme users as interviewees, 25 respondents of the target market that have tasted Tahuk! and 25 prospective target market respondents who have not tasted Tahuk!. The results of this study can be concluded that 88% of the respondents who have tasted Tahuk! gives a score of 8 and above. This is corroborated by statements from interviewees from extpert users and extreme users who say that there is no problem in terms of taste.